ANALISIS KETERAMPILAN DASAR BULUTANGKIS PB GEMILANG MATARAM TAHUN 2021 - Adi Wahyu Bimantara; Andi Gilang Permadi; Noor Akhmad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The problem of this research is that the basic skills of badminton athletes at PB Gemilang Mataram are still not good. This study aims to determine and analyze the level of basic badminton skills at PB Gemilang Mataram in 2021. This type of research is descriptive. The method used is a survey with data collection techniques using tests. The population in this study were athletes from PB Gemilang Mataram in the badminton branch in 2021, totaling 15 male athletes. The sampling technique in this study was purposive sampling. The criteria for determining this sample included: (1) athletes who were actively participating in training in 2021,. The instrument in this study consisted of a short serve test, a long serve test, a lob test and a smash test. The data analysis technique used descriptive analysis in the form of percentages. Results of basic skills 1). Short service for PB Gemilang Mataram badminton athletes in 2021, (1 person) in the "very high" category or 6.67%, (4 people) in the "high" category or 26.67%, (7 people) in the "medium" category or 46, 67%, (2 people) in the "less" category or 13.33%, and (1 person) in the "very poor" category or 6.67%. 2). long service badminton athlete PB Gemilang Mataram in 2021, (2 people) in the "very high" category or 13.33%, (2 people) in the "high" category or 13.33%, (7 people) in the "medium" category or 46, 67%, (3 people) in the "less" or 20% category, and (1 person) in the "very poor" category or 6.67%. 3). PB Gemilang Mataram badminton athlete lob shot in 2021, (5 people) in the "high" category or 33.33%, (5 people) in the "medium" category or 33.33%, (5 people) in the "less" category or 33.33 %. 4). PB Gemilang Mataram badminton athlete smash hits in 2021, (2 people) in the "very high" category or 13.33%, (8 people) in the "medium" category or 53.33%, (4 people) in the "less" category or 26, 67%, (1 person) in the “very poor” category or 6.67%.